Campylobacter jejuni as a bacterial cause of diarrhoea in Ile-Ife, NIgeria. - Olusanya, O. (Cambridge University Press, 1983)
A total of 495 diarrhoea and non-diarrhoea patients whose ages ranged between 5 and 39 years were examined for the presence of Campylobacter jejuni, Salmonella and Shigella species. About 12% of the specimens from diarrhoea patients were positive for Campylobacter jejuni compared with 6% and 10% for Salmonella and Shigella species. In contrast 2%, 0% and 1% of the samples from non-diarrhoea patients were positive for Campylobacter jejuni, Salmonella and Shigella species respectively. Most (62%) of the Campylobacter jejuni from diarrhoea patients were isolated from children under the age of 10 years. This compared with 26% and 37% for Salmonella and Shigella species in this age group. The frequency of isolation of Campylobacter jejuni in diarrhoea patients was highest during the dry months of the year. This study demonstrates the importance of Campylobacter jejuni as a major bacterial cause of diarrhoea in this part of the world.